Opsonic phagocytosis in chronic obstructive pulmonary disease is enhanced by Nrf2 agonists - Bewley, Martin A.; Budd, Richard C.; Ryan, Eilise; Cole, Joby; Collini, Paul; Marshall, Jennifer; Kolsum, Umme; Beech, Gussie; Emes, Richard D.; Tcherniaeva, Irina; Berbers, Gguy A.M.; Walmsley, Sarah R.; et al. (American Thoracic Society, 2018)
Rationale: Previous studies have identified defects in bacterial phagocytosis by alveolar macrophages (AM) in patients with chronic obstructive pulmonary disease (COPD) but the mechanisms and clinical consequences remain incompletely defined. Objectives: To examine the effect of COPD on AM phagocytic responses and identify the mechanisms, clinical consequences and potential for therapeutic manipulation of these defects. Methods: We isolated alveolar macrophages (AM) and monocyte-derived macrophages (MDM) from a cohort of COPD patients and controls within the MRC COPD-MAP consortium and measured phagocytosis of bacteria in relation to opsonic conditions and clinical features. Measurements and Main Results: COPD AM and MDM have impaired phagocytosis of S. pneumoniae. COPD AM have a selective defect in uptake of opsonized bacteria, despite the presence of anti-pneumococcal antibodies in bronchoalveolar lavage, not observed in MDM or healthy donor’s AM. AM defects in phagocytosis in COPD are significantly associated with exacerbation frequency, isolation of pathogenic bacteria and health related quality of life scores. Bacterial binding and initial intracellular killing of opsonized bacteria in COPD AM was not reduced. COPD AM have reduced transcriptional responses to opsonized bacteria, including cellular stress responses that include transcriptional modules involving antioxidant defenses and Nrf2-regualted genes. Agonists of the cytoprotective transcription factor Nrf2 (sulforaphane and Compound) reverse defects in phagocytosis of S. pneumoniae and non-type able Haemophilus influenzae by COPD. Conclusions: Patients with COPD have clinically relevant defects in opsonic phagocytosis by AM, associated with impaired transcriptional responses to cellular stress, which are reversed by therapeutic targeting with Nrf2 agonists.